Remembering the English Reformation in the Revision of the Communion Liturgy of the Book of Common Prayer, 1906–1920. (September 2019) - Cruickshank, Dan D.
This paper will examine how the Convocations of the Church of England remembered their past liturgies, and the reformation theology that formed the previous Prayer Books of the Church, in their main period of work on the revision of the Prayer Book from 1906 to 1920. Focusing on the Communion Service, it considers the lack of defenders of the 1662 Communion service and its reformed theology. It will examine how the 1549 Prayer Book was used as a basis for reordering the Communion service, and how this original Prayer Book was seen in relation to preceding medieval Roman Catholic theology. Ultimately it considers how a re-imagination of the English Reformation was used to justify the incorporation of liturgical theology that had no historical basis in the Church of England.